2014
DOI: 10.1136/neurintsurg-2014-011491
|View full text |Cite
|
Sign up to set email alerts
|

Risk of distal embolization with stent retriever thrombectomy and ADAPT

Abstract: BackgroundThere is a discrepancy in clinical outcomes and the achieved recanalization rates with stent retrievers in the endovascular treatment of ischemic stroke. It is our hypothesis that procedural release of embolic particulate may be one contributor to poor outcomes and is a modifiable risk. The goal of this study is to assess various treatment strategies that reduce the risk of distal emboli.MethodsMechanical thrombectomy was simulated in a vascular phantom with collateral circulation. Hard fragment-pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
157
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(163 citation statements)
references
References 35 publications
6
157
0
Order By: Relevance
“…25 Nonetheless, controversies about the relevance of the technique have arisen as in case of aspiration component failure, it might induce a potential delay in reperfusion which could have been avoided using the SR technique and also because this technique does not use a proximal flow arrest with Balloon guide catheter known to prevent embolus in new territory. 26,27 Although no comparative studies have been conducted with ADAPT versus the validated SR technique, some evidences suggest noninferiority 9 or superiority of the ADAPT technique to achieve better reperfusion rates. 7 In this perspective, more insights are needed to identify which patients may benefit from this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Nonetheless, controversies about the relevance of the technique have arisen as in case of aspiration component failure, it might induce a potential delay in reperfusion which could have been avoided using the SR technique and also because this technique does not use a proximal flow arrest with Balloon guide catheter known to prevent embolus in new territory. 26,27 Although no comparative studies have been conducted with ADAPT versus the validated SR technique, some evidences suggest noninferiority 9 or superiority of the ADAPT technique to achieve better reperfusion rates. 7 In this perspective, more insights are needed to identify which patients may benefit from this technique.…”
Section: Discussionmentioning
confidence: 99%
“…These rates of embolic complications are within the range of previous reports either in vitro or on patients' cohorts. 26 Improvements of the technique especially with development of larger less traumatic, with better trackability catheters, to decrease the needs for SR are required. Improvements in logistics, with patients more rapidly in the odds ratio, could have an impact on the efficacy of the aspiration component technique.…”
Section: Strokementioning
confidence: 99%
“…However, our sample size was limited; experimental work suggests that a combined strategy with aspiration with adjunct stent retrievers may decrease the rate of embolization in a new territory. 23 Symptomatic hemorrhagic complications, defined in this study as an ECASS-evident intracranial hemorrhage with an increase of Ն4 on the NIHSS scale at 24 hours from baseline, were lower after the ADAPT approach. Study results yielded symptomatic intracranial hemorrhage rates (2.4% for ADAPT versus 5.9% for Solitaire) similar to those of recent randomized controlled trials studying stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of the latest thrombectomy devices, microemboli may still be found in cerebral arterioles downstream from the treated vessel. 12,13 Intravenous antiplatelet agents may suppress local microthrombus and microembolus formation, but clinical trial results have not demonstrated improved outcomes. Rather, they have highlighted an increased risk of intracranial hemorrhage after the combined use of antiplatelet agents and pharmacological fibrinolysis.…”
mentioning
confidence: 99%